Knowledge, attitude, and practice towards obesity among the general public in community settings of Tirupati: a cross-sectional study - Moorthy, Srinivas B. R.; Subbaiahgari, Harini; Sibbala, Pavani; Kola, Sravani; Kareem, Liyakath (International Journal of Advances in Medicine, 2022)
Background: Obesity and overweight are strongly linked to developing diabetes, hypertension, myocardial infarction, stroke, and endocrine disorders. Knowledge, attitude, and practices of the public are crucial in limiting the burden of obesity in the Indian community. The current study aims to assess the KAP of obesity among the general public of India. Methods: A community-based cross-sectional survey was conducted in the rural and urban areas of Tirupati city. Adults aged 18 years or above who are willing to participate, were included. A total of 300 subjects were enrolled and data was collected by using a pre-validated questionnaire. Variables like weight, height and KAP scores were obtained. Chi-square tests were used to associate demographics with good KAP towards obesity. Results: The findings show that more than half of the participants have good knowledge, and a positive attitude, but the practices are not optimal in dealing with obesity and management. Participants’ ages more than 40 years, presence of comorbidity, risk factors, and social habits are significantly associated with obesity and overweight. Obese are having good knowledge but normal-weight people are significantly associated with a positive attitude. Participants of normal weight, no risk factor, and no habits were significantly associated with rational practices. Conclusions: The study concludes that the participants had good knowledge and attitude toward obesity but the participants failed to practice controlling and preventing obesity. However, more efforts are required in creating awareness and educating the general population regarding physical activity, diet, and lifestyle in preventing obesity and its associated complications.